2020
DOI: 10.1039/d0ra09895g
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure synthesis of ε-FeOOH from β-FeOOH and its application to the water oxidation catalyst

Abstract: Research on materials under extreme conditions such as high pressures provides new insights into the evolution and dynamics of the earth and space sciences, but recently, this research has focused on applications as functional materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…In some cases, it also functions as a passivation layer to suppress electron−hole recombination or a hole transfer layer. 28−31 To achieve higher efficiency, further endeavors, such as cation/anion doping, 32−34 oxygen vacancies introduction, 35,36 and phase structure transition, 37,38 have been dedicated. In particular, elemental doping can be used to modulate the electronic structure of surrounding metal active species and boost the catalytic activity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, it also functions as a passivation layer to suppress electron−hole recombination or a hole transfer layer. 28−31 To achieve higher efficiency, further endeavors, such as cation/anion doping, 32−34 oxygen vacancies introduction, 35,36 and phase structure transition, 37,38 have been dedicated. In particular, elemental doping can be used to modulate the electronic structure of surrounding metal active species and boost the catalytic activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…According to the previous literature, FeOOH can exhibit genuine catalytic behavior to reduce the overpotential of the OER reactions. In some cases, it also functions as a passivation layer to suppress electron–hole recombination or a hole transfer layer. To achieve higher efficiency, further endeavors, such as cation/anion doping, oxygen vacancies introduction, , and phase structure transition, , have been dedicated. In particular, elemental doping can be used to modulate the electronic structure of surrounding metal active species and boost the catalytic activity. , Kim and co-workers found that the incorporation of Mn into FeOOH leads to an increase in active surface area and intrinsic activity by modulating the electronic structure of FeOOH .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a platform of earth-abundant-based nanostructured materials has attracted great attention for catalysis, sensing, and energy conversion applications. [24][25][26][27][28][29][30] Further, nanostructured materials architecture has several advantages in terms of size reduction or pores creation, which improve charge transfer and electrochemical reaction mechanisms. 31,32 In this regard, iron oxide nanostructured electrocatalysts have been investigated for energy conversions within water splitting due to their catalytic performance, low cost, non-toxicity, good stability, and excellent physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…N-type semiconductors such as TiO 2 , BiVO 4 , and α-Fe 2 O 3 or molecular dyes such as ruthenium tris-bipyridine complexes, , perylene, , polyheptazine, , metal-free porphyrins, and π-conjugated naphthalene benzimidazole polymers have been assayed as PSs in this context. Regarding the OER catalyst, oxides of transition metals such as IrO 2 , , CoO x , , Co–Pi, or FeOOH have been investigated, as well as some molecular complexes. , …”
Section: Introductionmentioning
confidence: 99%
“…Since then, only a few other systems were published. , Recently, our group also investigated this approach and reported the covalent grafting of a Ru complex PS onto Co 3 O 4 NPs, using pendant phosphonate linkers and its positive impact on the photoanode efficiency . We then expanded our work toward more environment-friendly catalysts, such as iron-based systems, considering that iron oxides , and iron oxohydroxides have been reported to be active and stable electrocatalysts for the OER, but that none of these materials have been used so far to build a hybrid photoanode by combination with a molecular PS.…”
Section: Introductionmentioning
confidence: 99%